A SOCIO-PRAGMATIC STUDY OF PHATIC UTTERANCE IN MOVIE ENTITLED THE SECRET LIVE OF PETS - Dwi Purnamasari; Dwi Aji Prajoko (Universitas Katolik Widya Mandala Surabaya, 2021)
The research aimed to describe the phatic utterance functions expressed by the characters in themovie entitled The Secret Life of Pets. This was descriptive-qualitative research. The data of thestudy were the words, phrases, and clauses expressing the phatic utterances in the movie. Thedata collection technique was content analysis. The data analysis technique was ethnographic;therefore, domain analysis, taxonomy analysis, componential analysis, and cultural themeanalysis were carried out. The data was analyzed on the basis of the socio-pragmatic approach.The research showed that there were four functions of phatic utterances found in the movieentitled The Secret Life of Pets, namely breaking the silence, having small talks, keeping theconversation going, and expressing solidarity; the most dominant function was breaking thesilence. Breaking the silence as the dominant phatic utterance strengthened the notion thatphatic utterance was not informational. This dominance was closely related to the object of theresearch in which breaking the silence followed by having small talks were very important intheir everyday life.Â Â Key words: socio-pragmatics, phatic utterances functions